Biological control of powdery mildew in greenhouse produced cucumber : an evaluation of two microbiological control agents - Almqvist, Anna-Carin (SLU/Dept. of Plant Breeding (from 130101), 2013)
Powdery mildew is a serious problem in both field and greenhouse cucumber production and can cause serious infection and radically reduced yields. Today, powdery mildew is the main disease in greenhouse produced cucumber. Disease control should preferably be both efficient and environmentally friendly, which is not easy to achieve at all times. Alternatives to chemical control of powdery mildews are biological control, physical control, non-fungicide control and cultivation of resistant or tolerant varieties. Biological control can be described as the suppression of damaging activities inflicted of a harmful organism by one or more other organisms, which are called antagonists or natural enemies. In Sweden, there are currently no registered biological control products available to control cucumber powdery mildew. The aim of this study was to investigate the effect of two biological control products in order to evaluate their ability to prevent or reduce powdery mildew infection to an acceptable level in greenhouse produced cucumber. In the experiments, different application regimes were also studied. The active organisms in both tested products are fungi. In one of the products the active organism was Ampelomyces quisqualis and in the other Pythium oligandrum. The fungal species causing the powdery mildew in the experiments was characterized. The present report consists of a literature study, an experimental part and a microscope study. Trials were performed in a greenhouse at a conventional cucumber grower’s site at Sånnagården, Kvidinge, and in a chamber in one of the greenhouses at the Swedish University of Agricultural Sciences, Alnarp. In this study, some of the biocontrol treatments could prevent and reduce powdery mildew attacks to an acceptable level in greenhouse produced cucumber. The effect of using the biocontrol agents prophylactically was significantly better with P. oligandrum compared to the untreated control but not with A. quisqualis. The effect of using A. quisqualis with an application interval of fourteen days was significantly better compared to a seven days application interval. For P. oligandrum, there was no difference between the two application intervals. The fungus causing the powdery mildew symptoms in this experimental study was most probably Golovinomyces cichoracearum.